The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1111/jtxs.12599
|View full text |Cite
|
Sign up to set email alerts
|

Increased viscosity of milk during infant feeding improves swallow safety through modifying sucking in an animal model

Abstract: Infants experiencing frequent aspiration, the entry of milk into the airway, are often prescribed thickened fluids to improve swallow safety. However, research on the outcomes of thickened milk on infant feeding have been limited to documenting rates of aspiration and the rheologic properties of milk following thickening. As a result, we have little insight into the physiologic and behavioral mechanisms driving differences in performance during feeding on high viscosity milk. Understanding the physiologic and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 60 publications
3
12
0
Order By: Relevance
“…Often, infants exhibiting feeding difficulties are prescribed nipples with lower flow rates (Mathew & Cowen, 1988; Pados et al, 2015). Alternatively, infants with feeding difficulties are often fed milk with increased viscosity, which reduces the frequency of aspiration (Cichero et al, 2013; Mayerl et al, 2021; Newman et al, 2016). One limitation of these interventions is that they do not necessarily treat the underlying etiologies that generate feeding difficulties (Mayerl et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Often, infants exhibiting feeding difficulties are prescribed nipples with lower flow rates (Mathew & Cowen, 1988; Pados et al, 2015). Alternatively, infants with feeding difficulties are often fed milk with increased viscosity, which reduces the frequency of aspiration (Cichero et al, 2013; Mayerl et al, 2021; Newman et al, 2016). One limitation of these interventions is that they do not necessarily treat the underlying etiologies that generate feeding difficulties (Mayerl et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Pigs received an infant pig milk replacer formula (Solustart Pig Milk Replacement; Land o' lakes, Arden Mills) for the duration of the experiments. Additional housing and feeding followed care guidelines previously outlined but are standard for this animal model (Holman et al, 2013; Mayerl et al, 2021).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies related to infants and increased viscosity are concerned with the physical effects increasing viscosity has on physical properties of milk or formula such as the flow rate, rheology, and thickener compatibility (Almeida et al, 2017; Koo et al, 2019; September, 2021). But few studies have investigated the effect of changing viscosity on swallow performance or physiology in infants (German et al, 1998; Goldfield et al, 2013; Mayerl, Edmonds, et al, 2021). Goldfield et al (2013) found that infants alter the movements of the tongue and soft palate relative to each other in response to different viscosities, which they hypothesize improves the efficacy of the pumping motion.…”
Section: Introductionmentioning
confidence: 99%
“…Dysphagia among infants has also been a major concern for a long time. Two research articles are included in this special issue to reflect new progresses on the texture modification of infant milk: Viscosity of milk during infant feeding improves swallow safety (Mayerl, Edmonds, Gould, & German, 2021) and the effect of commercially available thickening agents on ready-to-feed infant formulas (Gosa & Choquette, 2021).…”
mentioning
confidence: 99%